Evaluation of postoperative clinical outcomes in Jehovah's Witness patients who receive prothrombin complex concentrate during cardiac surgery. Issue 4 (12th February 2020) - Harris, Jesse E.; Varnado, Sara; Herrera, Elizabeth; Salazar, Eric; Colavecchia, Anthony C.
Abstract: Background: Patients who refuse allogeneic blood transfusions (alloBT) on the basis of religious doctrine, such as Jehovah's Witnesses (JWs), can pose a challenge when undergoing surgical procedures. During cardiac surgery, special considerations regarding surgical techniques and blood loss minimization strategies can lead to improved outcomes. Limited literature exists to guide the use of four‐factor prothrombin complex concentrate (4PCC) in this patient population undergoing cardiac surgery. Study Design and Methods: This retrospective, single‐center study evaluated the impact of 4PCC on hemoglobin (Hgb) change from baseline to postoperative nadir within a 7‐day period among patients who refused alloBT during cardiac surgery. This study identified patients who refused alloBT from January 2011 to June 2017. Multivariable linear regression was used to control for confounding variables to evaluate the effectiveness of 4PCC. Results: During the study timeframe, 79 patients met inclusion criteria, all of whom identified as JWs, and underwent cardiac surgery. Of these, 19 received intraoperative 4PCC. Multivariable linear regression found no difference in Hgb change in patients who received 4PCC vs those who did not. No significant differences were found in mortality, thromboembolic complications, or in‐hospital postoperative events. Conclusions: In JWs undergoing cardiac surgery who refuse alloBT, intraoperative use of 4PCC was not associated with a difference in Hgb change within 7 days postoperatively when adjusting for confounding variables. In the event of excessive blood loss, the utilization of 4PCC may provide a viable option in JW patients who undergo cardiac surgery where few options exist to mitigate blood loss.